On the Export Trade of Indian Rosewood - Sivarajan, M. (Indian Forester, 1969)
The importance of Indian rosewood (Dalbergia latifolia Roxb.) as an export commodity and the threat posed by its rival species in the international market have been discussed. The past history of the export trade of this wood has been reviewed analysing the causes for the increase in trade during the "Golden age" and for the sudden decline thereafter. The recent trends in the international market and the increasing prospects for the export of this wood to Japan and other countries is different formm have been discussed. The different measures under contemplation for the introduction of quality control and standardisation for export quality rosewood both in log and veneer forms have been outlined discussing their merits and practicability. The importance to ensure regeneration of this valuable species which earns a lot of foreign exchange has been stressed.